Study guides

☆☆

Q: How do you simplify -7n plus 9n?

Write your answer...

Submit

Still have questions?

Related questions

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

10n = 7n + 4 + 2n so 10n = 9n + 4 Subtract 9n from both sides: n = 4

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

n - 10 + 9n - 3 n + 9n - 10 - 3 10n - 13

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9

You can only simplify sorry not solve. 8m+4n−6m+9n =8m+4n+−6m+9n Combine Like Terms: =8m+4n+−6m+9n =(8m+−6m)+(4n+9n) =2m+13n

-5 plus 9n plus 6 is 1 plus 9n.

Solve 5n+4n+32: Simplify the expression. 4n+5n+32=0; 9n+32=0 Group all constants on the right side of the equation. 9n+32=0; 9n+32-32=0-32; 9n=0-32; 9n=-32 Isolate the n. 9n=-32; 9n/9=-32/9; n=-32/9

-7n - 8 + 6 = 13 - 2 Add 2 to each side: -7n - 8 + 6 + 2 = 13 simplify: -7n = 13 n = -13/7 = -16/7

63

If it is: 13m+5n-6m+9n Then simplified it is: 7m+14n

9n + n = 10n

People also asked